RANCANGAN MEDIA INTERAKTIF PAZUKA-GEMU UNTUK PEMBELAJARAN KANJI N5 - Fadian Fitriana, Zian Andra; Setiana, Soni Mulyawan (Mahadaya: Jurnal Bahasa, Sastra, Dan Budaya, 2023)
This study aims to determine the design of the Pazuka-Gemu interactive media for learning Kanji N5. The media was created using the Adobe Flash CS6 application. And the method that the author uses in this study uses the ADDIE model development method (Analysis, Design, Development, Implementation, and Evaluation). This media contains about learning kanji with puzzle games. In this study, there is an explanation of the Pazuka-Gemu interactive media starting from the display design to the credit menu. This media is designed to help students in learning Kanji N5 in understanding the kanji material. The material in the media is taken from the Kanji Master book and Sematskill.com Web. The conclusion from the results of this study is that the Pazuka-Gemu interactive media design has been successfully implemented so that the media can run well. Keywords: Kanji N5, Puzzle Game, Learning Media, Adobe Flash CS6